Considerations surrounding remote medicolegal assessments: a systematic search and narrative synthesis of the range of motion literature. Issue 1 (23rd April 2021) - Steadman, Peter; Sheppard, Dianne; Henderson, Janette; Halliday, Brett; Freckelton, Ian
Abstract: Remote telehealth practices were forced to advance 10 years in a few short weeks in March 2020 due to the onset of a global pandemic. In the sphere of non‐clinical medicine, a dramatic element of uncertainty entered the psyche of doctors and lawyers in relation to the validity of remote or virtual independent medical examination (vIME). This paper considers the key issues surrounding the virtual assessment of clients for medicolegal purposes. Our main hypothesis was that, within certain defined parameters, the vIME technique can deliver reliable and accurate assessments. To explore this, a systematic literature search focusing on advanced device‐based range of motion measurement was conducted, along with an historical snapshot of observation‐based range of motion measurement considering application to remotely performed IME. While some specialists are of the view that observational measurement may be applied reliably to some joints when conducted by experienced orthopaedic surgeons, evidence for this is scant. The results, instead, support the notion of using task substitution, that is specialists appropriately assisted in conducting vIMEs by musculoskeletal trained allied health practitioners, regardless of the measurement tool, for permanent impairment assessments. Moreover, self‐performed examinations by injured individuals using advanced technology are not reliable in this setting. Our final contention is that remote examinations with limited clinical assessment have utility for legal matters, such as the assessment of causation of injury, treatment advice or approvals and fitness for pre‐employment tasks or safe variations, with objective clinical adjunct support such as Picture Archiving and Communication System‐based modern radiology systems. Abstract : This paper addresses a previously unexplored gap in considering the potential for remote or virtual independent medical examinations (vIME), and is a step towards demonstrating that best practice vIME techniques, within certain defined parameters, can deliver reliable and accurate assessments. The key elements of this manuscript include: a systematic literature search focusing on advanced device‐based range of motion measurement, and an historical snapshot of observation‐based measurement considering application to remotely performed IME.